2018
DOI: 10.3390/rs10071159
|View full text |Cite
|
Sign up to set email alerts
|

Interdependent Dynamics of LAI-Albedo across the Roofing Landscapes: Mongolian and Tibetan Plateaus

Abstract: The Mongolian Plateau (MP) and Tibetan Plateau (TP) have experienced higher-than-global average warming in recent decades, resulting in many significant changes in ecosystem structure and function. Among them are the leaf area index (LAI) and albedo, which play a fundamental role in understanding many causes and consequences of land surface processes and climate. Here, we focused on the spatiotemporal changes of LAI, albedo, and their spatiotemporal relationships on the two roofing landscapes in Eurasia. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…6a) For the LAI in the study 17years, the resulting of line regression for four vegetation community types showed increasing trend in annual and most month, especially for TPL in annual, July and August, and for MDW in July and August (Fig.. 2a). This result was conformable with other papers on the MP (Chen et al, 2015;John et al, 2018;Qi, 2017;Shao et al, 2017b;Shen et al, 2015;Tian et al, 2018). However from the month change of slope in the study years in May and September, we did not found the growing season extrension over there.…”
Section: Fig6 the Line Regression Of Average Annual Albedo And Et Rsupporting
confidence: 93%
“…6a) For the LAI in the study 17years, the resulting of line regression for four vegetation community types showed increasing trend in annual and most month, especially for TPL in annual, July and August, and for MDW in July and August (Fig.. 2a). This result was conformable with other papers on the MP (Chen et al, 2015;John et al, 2018;Qi, 2017;Shao et al, 2017b;Shen et al, 2015;Tian et al, 2018). However from the month change of slope in the study years in May and September, we did not found the growing season extrension over there.…”
Section: Fig6 the Line Regression Of Average Annual Albedo And Et Rsupporting
confidence: 93%
“…The uncertainty in the meteorological forcing data clearly affected the simulation of vegetation growth process in LSMs (Li et al, 2019), and eventually induced bias in GPP estimation. For example, the LAI derived from MODIS product was reported to be averagely 0.70 during 2000–2015 in the TI region (Tian et al, 2018), while the simulated LAI in the present study was larger than MODIS in the majority area of TI region (Figure S8), with the mean annual value being 0.94–0.98 and 1.38–1.47 from simulations with CRUF and CHNF data, respectively. Compared to the CRUF data, the CHNF data, with higher air temperature (Figure S9), induced higher simulated LAI and subsequently resulted in higher simulated GPP in the TI region (Figure S2).…”
Section: Discussionmentioning
confidence: 46%
“…Journal of Geophysical Research: Atmospheres 2000-2015 in the TI region (Tian et al, 2018), while the simulated LAI in the present study was larger than MODIS in the majority area of TI region ( Figure S8), with the mean annual value being 0.94-0.98 and 1.38-1.47 from simulations with CRUF and CHNF data, respectively. Compared to the CRUF data, the CHNF data, with higher air temperature ( Figure S9), induced higher simulated LAI and subsequently resulted in higher simulated GPP in the TI region ( Figure S2).…”
Section: 1029/2020jd033476mentioning
confidence: 50%
“…Some studies clearly demonstrated that the surface albedos of different plant species show different spatial and temporal patterns due to different canopy architecture and composition optical properties (Betts, ; Gao et al, ; Kuusinen et al, ; Kuusinen et al, ; Tian et al, ; Yanagi & Costa, ). For instance, there exists a general negative logarithmic relationship between LAI and the albedo on both the Mongolian Plateau and Tibetan Plateau (Tian et al, ); the foliage and branches clumping at the shoot and crown level can increase the probability for multiple interactions of photons in the canopy, thus reducing forest albedo (Hovi et al, ). The variability of snow‐free surface albedo is greatly determined by the optical contrast between the vegetation canopy and the background soil, and vegetation cover over bright‐colored soils reduces the surface albedo, whereas plants on dark soils increase the surface albedo (Rechid et al, ).…”
Section: Introductionmentioning
confidence: 99%